2020
DOI: 10.1007/s11356-020-12094-z
|View full text |Cite
|
Sign up to set email alerts
|

Progestogen-induced alterations and their ecological relevance in different embryonic and adult behaviours of an invertebrate model species, the great pond snail (Lymnaea stagnalis)

Abstract: The presence of oral contraceptives (basically applying estrogens and/or progestogens) poses a challenge to animals living in aquatic ecosystems and reflects a rapidly growing concern worldwide. However, there is still a lack in knowledge about the behavioural effects induced by progestogens on the non-target species including molluscs. In the present study, environmental progestogen concentrations were summarised. Knowing this data, we exposed a well-established invertebrate model species, the great pond snai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Embryos <4 days old (E45 as per the staging method employed in Voronezhskaya et al, 1999) exhibited no signal with respect to TH expression (data not shown). Four‐day‐old larvae began to develop eyes, and the development of the foot and shell became distinct (Hohagen & Jackson, 2013; Ivashkin et al, 2015; Jackson et al, 2016; Mescheryakov, 1990; Morrill, 1982; Svigruha et al, 2021). TH expression became detectable in two cells in the anterior region of the head at 5 days after first cleavage (Figure 2A–C), in the remnants of the apical organ of the larval nervous system, which is present only prior to metamorphosis (Nielsen, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Embryos <4 days old (E45 as per the staging method employed in Voronezhskaya et al, 1999) exhibited no signal with respect to TH expression (data not shown). Four‐day‐old larvae began to develop eyes, and the development of the foot and shell became distinct (Hohagen & Jackson, 2013; Ivashkin et al, 2015; Jackson et al, 2016; Mescheryakov, 1990; Morrill, 1982; Svigruha et al, 2021). TH expression became detectable in two cells in the anterior region of the head at 5 days after first cleavage (Figure 2A–C), in the remnants of the apical organ of the larval nervous system, which is present only prior to metamorphosis (Nielsen, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…From these stock solutions, 100 ng mL −1 working solutions were prepared in ethanol and then added in the appropriate volume to the experimental glass beakers to reach the desired nominal equi-concentration of 10 ng L −1 (mixture of progestogens) (≤ 0.01 % final solvent concentration). The 10 ng L −1 concentration value represents the detectable concentration level of the three compounds in Lake Balaton and its catchment area (Avar et al, 2016b;Maasz et al, 2019) as well as reflects to the average global concentration values (Svigruha et al, 2021a).…”
Section: Mps and Chemicals For Chronic Exposuresmentioning
confidence: 99%
“…Previous environmental analytical studies revealed the presence of many PhACs in Lake Balaton and its catchment area (Avar et al, 2016a;Avar et al, 2016b;Maasz et al, 2019;Maasz et al, 2021;Molnar et al, 2021). Moreover, of the detected PhACs, previous studies investigated the impact of progestogens (progestogen and its synthetic analogues) on invertebrate (water flea [Daphnia magna] and the great pond snail [Lymnaea stagnalis]) and vertebrate (roach [Rutilus rutilus]) aquatic species representing the ecosystem of Lake Balaton and demonstrated several effects from the behavioral to the molecular level (Maasz et al, 2017;Svigruha et al, 2021b;Svigruha et al, 2021a;Zrinyi et al, 2017). However, similar surveys regarding MPs have not yet been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Steroid hormones are known as active chemical compounds that are involved in all the significant physiological roles in the body of living organisms 1 . These roles include the development of sexual characteristics, regulation of cell activity, mood control, water balance in the body, stimulation of the metabolism activities and growth, among others 2 – 4 . Steroid hormones are classified into four groups based on their structural variation and affinities 5 .…”
Section: Introductionmentioning
confidence: 99%